Precision analysis of forced-oscillation device: numerical modelling and experimental investigations. (19th October 2020) - Li, Hui; Lin, Jing; Gao, Jinghuai; He, Yanbin; Han, Dehua; Zhao, Luanxiao
Abstract: Investigating the stress state of a sample-standard column in forced-oscillation apparatus is critical to clearly quantify measurement credibility, offering insights into revealing intrinsic frequency-dependent elastic characteristics of a rock sample. To investigate the effects of the jointing condition, the location of strain gauges and device resonance on the stress state of a sample-standard column, we experiment with a typical forced-oscillation setup numerically and experimentally at frequencies of 2–800 Hz. Overall, the numerical model captures the primary features of the forced-oscillation device, which makes the simulated data fit well with the measured results. Meanwhile, based on the configuration of the sample-standard column with variable static friction in jointing contacts, the simulated results also indicate that mechanical contacts of the sample-standard-vibrator assembly lead to stress concentration, resulting in coordinate-dependent strains on both the sample and standard. Additionally, strain magnitude is also frequency-dependent, causing a relatively large measurement error on the elasticity of the sample at higher frequencies. Ultimately, numerical results not only optimize measurement workflow but also create a solid foundation for the interpretation of measured data.